2013
DOI: 10.3109/21681805.2013.813963
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in long-term survivors after renal cancer treatment

Abstract: The results show that RCC patients, and in particular those treated by a flank approach but not those treated by minimal invasive surgery, have a multifacetedly reduced HRQoL compared to a general population cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Besides, they also reported that the percentage of nancial di culties of urologic cancer survivors was higher than that in controls(16). Beisland et al demonstrated that long-term survivors after renal cancer treatment had worse scores on fatigue, pain, sleep, nausea and vomiting, constipation and diarrhea than other groups (17). All of these ndings were consistent with ours, making our results more reliable.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, they also reported that the percentage of nancial di culties of urologic cancer survivors was higher than that in controls(16). Beisland et al demonstrated that long-term survivors after renal cancer treatment had worse scores on fatigue, pain, sleep, nausea and vomiting, constipation and diarrhea than other groups (17). All of these ndings were consistent with ours, making our results more reliable.…”
Section: Discussionsupporting
confidence: 90%
“…KC survivors showed significantly lower physical functioning than that observed in the general population. To date, only two studies [21,22] have compared HRQoL between KC survivors and non-cancer controls and have reported conflicting results: a study performed in the United States [21] using the 36-Item Short Form Health Survey (SF-36) and the RAND-12 questionnaire (vs. the EORTC QLQ-C30 used in our study) showed no significant differences in the HRQoL between the two study groups, and a Norwegian study [22] showed that KC survivors, particularly those undergoing surgery via an open or a flank approach, showed a lower HRQoL including a significantly higher pain score than that observed in the general population [22]. Our study also showed higher pain and dyspnea symptoms among KC survivors (among these, 43.5% [47/108] underwent open surgery).…”
Section: Discussionmentioning
confidence: 99%
“…From the 1404 identified citations, 16 observational comparative studies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 1 RCT [31] met the inclusion criteria. The PRISMA diagram depicts the flow of the literature selection (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the studies and the patients, PROMs used, time-points of evaluation, outcomes, confounders, and variables of interest of the included studies are summarized in Tables 2 and 3. Eleven studies included exclusively LRCCs [16][17][18]20,23,[25][26][27][28][29]31] and 6 LRMs [15,19,21,22,24,30]. There were 6 longitudinal [15,17,21,22,26,30] and 9 cross-sectional studies [16,[18][19][20]24,25,[27][28][29].…”
Section: Resultsmentioning
confidence: 99%